2016
DOI: 10.7863/ultra.16.02013
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Sonography of Hematologic Malignancies of the Testis: Grayscale, Color Doppler, and Contrast‐Enhanced Ultrasound and Strain Elastographic Appearances With Histologic Correlation

Abstract: Primary testicular lymphoma is rare and appears with nonspecific findings on grayscale and color Doppler sonography. We present 8 patients further examined with contrast-enhanced sonography, strain elastography, and histologic analysis after orchiectomy. Seven of 8 patients had a diagnosis of large B-cell lymphoma, and 1 of 8 had a diagnosis of granulocytic sarcoma, with solitary lesions (2 of 8), multiple lesions (3 of 8), or entire testicular involvement (3 of 8). Lesions appeared hypoechoic (7 of 8) or isoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…In our study, the VES demonstrated a specificity of 45.5% in diagnosing malignancy and 57.89% in diagnosing neoplasms. We observed hard SE characteristics in a number of nonneoplastic lesions including cysts, hematomas, infarctions, rete testis, and scars (Figure ); in all of these etiologies, hard elastographic properties have been previously reported …”
Section: Discussionsupporting
confidence: 70%
“…In our study, the VES demonstrated a specificity of 45.5% in diagnosing malignancy and 57.89% in diagnosing neoplasms. We observed hard SE characteristics in a number of nonneoplastic lesions including cysts, hematomas, infarctions, rete testis, and scars (Figure ); in all of these etiologies, hard elastographic properties have been previously reported …”
Section: Discussionsupporting
confidence: 70%
“…Moreover, CEUS increases the accuracy of ultrasound on tumor blood supply determination 1617. However, the scrotal ultrasonography with a combination of gray-scale and color Doppler techniques has still been the first-line imaging modality for evaluation of testicular tumors because of its low cost, wide availability, and high diagnostic accuracy 1819. In summary, as a noninvasive examination, scrotal ultrasonography may greatly increase the diagnostic accuracy of testicular tumors and should be considered as the primary preoperative examination for all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of six patients with histological confirmation of primary testicular lymphoma, all lesions appeared hard; five of six showed a VES of 5, and the other had a VES of 4 (Fig. 5) [18].…”
Section: Testicular Neoplastic Lesionsmentioning
confidence: 99%